2021
DOI: 10.3889/oamjms.2021.5663
|View full text |Cite
|
Sign up to set email alerts
|

Serum Level of Uromodulin as an Early Predictor Marker of Kidney Disorders

Abstract: BACKGROUND: Metabolic diseases are known to be risk factors of kidney injury. The glycoprotein Uromodulin Tamm-Horsfall protein is a biochemical marker specifically synthesized and secreted by kidney tubular epithelial cells. AIM: The study aimed to use novel biochemical parameters to predict early changes in renal functions and to use natural food supplements to help in the prevention and management of such conditions. METHODS: Crossover studies comparing two interventions trials. Subjects: Sevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…El-Shebini et al [42] used serum Uromodulin (sUMOD) as a novel biochemical marker to predict early changes in renal functions in obese participants and evaluate the effect of using dietary supplement made of special herbs and whole grains to help in the prevention and management of such conditions. The results showed that the measurement of the sUMOD proved to be an accurate and precise biochemical parameter to show the speed of the renal response to the management by comparison with using usual diagnostic old markers.…”
Section: New Renal Biomarkersmentioning
confidence: 99%
“…El-Shebini et al [42] used serum Uromodulin (sUMOD) as a novel biochemical marker to predict early changes in renal functions in obese participants and evaluate the effect of using dietary supplement made of special herbs and whole grains to help in the prevention and management of such conditions. The results showed that the measurement of the sUMOD proved to be an accurate and precise biochemical parameter to show the speed of the renal response to the management by comparison with using usual diagnostic old markers.…”
Section: New Renal Biomarkersmentioning
confidence: 99%